CAESAREA. EXPERIENCE IN THE GENERAL HOSPITAL OXAPAMPA - Echáis, José Fernando (2015)
OBJECTIVE.- To determine the main indícations and complications of cesarean deliveries. MATERIAL AND METHODS.- Retrospective study that revíewed the clinical and perinatal histories of 109 patients who underwent cesarean sectíon at Oxapampas General Hospital trom January 2001 to December 2002. Maternal and neonatal variables were analyzed using percentage and frequency tables. RESULTS: The cesarean delivery rate was 25,7%, The majority of the patients were between 20 and 35 years-old (56,9%), had primary education (35,8%), were not married (54,%) and had a term pregnancy (77,6%). The most frequent indications forcesarean delivery were cephalopelvic disproportion (21,1%), fetal distress (20,2%), previous cesarean section (11,9%), and breechpresentation (9,296). Seven patients (6,3%)presented puerperal morbidity and endometritís and surgical wound infection were the most frequent complications (28,6%). There were no maternal deaths. The perinatal mortality rate was 8,7 deaths per 1000 births. CONCLUSIONS.- The cesarean delivery rate was 25,7%. The most frequent indications for cesarcan delivery were cephalopelvic disproportion, fetal distress, previous cesarean section and breech presentation. The main complications were puerperal endometritis and surgical wound infection.